Redesign of genetically encoded biosensors for monitoring mitochondrial redox status in a broad range of model eukaryotes - Albrecht, Simone Christine; Bausewein, Daniela; Hell, Rüdiger; Meyer, Andreas (Journal of biomolecular screening, 2013)
The development of genetically encoded redox biosensors has paved the way toward chemically specific, quantitative, dynamic, and compartment-specific redox measurements in cells and organisms. In particular, redox-sensitive green fluorescent proteins (roGFPs) have attracted major interest as tools to monitor biological redox changes in real time and in vivo. Most recently, the engineering of a redox relay that combines glutaredoxin (Grx) with roGFP2 as a translational fusion (Grx1-roGFP2) led to a biosensor for the glutathione redox potential (EGSH). The expression of this probe in mitochondria is of particular interest as mitochondria are the major source of oxidants, and their redox status is closely connected to cell fate decisions. While Grx1-roGFP2 can be expressed in mammalian mitochondria, it fails to enter mitochondria in various nonmammalian model organisms. Here we report that inversion of domain order from Grx1-roGFP2 to roGFP2-Grx1 yields a biosensor with perfect mitochondrial targeting while ...
Gesehen am 27.01.2017